Kepatuhan Syariah (Sharia Compliance) dalam Industri Keuangan Syariah - Luqman Nurhisam (Jurnal Hukum IUS QUIA IUSTUM, 2016)
The fact that it is obliged to Sharia Supervision Board (DPS) in every Sharia Bank Financial Industry (IKBS) and non-bank financial industry (IKNBS) to abide by sharia conditions has made sharia supervision inseparable from sharia compliance. Such thing can be seen from several regulations issued by DPS-MUI which become a reference for IKBS and IKNBS in running their activities in the sector of sharia finance. This research focuses on the regulations issued by DSN-MUI and their implementation regarding IKBS IKNBS, as well as DPS as the one having the authority to supervise every sharia-based finance industry. This was a normative research, which searches for data in the form of books and other written data which have correlation with the research object by using descriptive-analytic approach. The findings show that DPS as the one having the authority to supervise sharia compliance, has responsibility as stated by a strict legal system. The existence of DPS really determines the establishment of sharia compliance, which becomes the main unsure in the existence and continuity of syariah financial industry.